The Power of Henry's Imagination - Byrne, Skye; Illustration by George, Nic (New York Simon And Schuster, 2015)
When Henry's beloved stuffed rabbit, Raspberry, goes missing, he enlists his whole family to help him search for the missing toy. But Raspberry can't be found. Then Henry's grandfather suggests that Henry use his imagination to find his rabbit. Will the power of Henry's imagination bring Raspberry back? Or is Raspberry gone for good?
Include Color Illustration
Keywords: Imagination -- Lost articles -- Positive psychology